Coinfection by Severe Acute Respiratory Syndrome Coronavirus 2 and Influenza A(H1N1)pdm09 Virus Enhances the Severity of Pneumonia in Golden Syrian Hamsters - Jinxia Zhang; Andrew Chak-Yiu Lee; Jasper Fuk‐Woo Chan; Feifei Liu; Can Li; Yanxia Chen; Hin Chu; S. Lau; Pui Wang; Chris Chung-Sing Chan; Vincent Kwok‐Man Poon; Shuofeng Yuan; et al. (2020)
Abstract Background Clinical outcomes of the interaction between the co-circulating pandemic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and seasonal influenza viruses are unknown. Methods We established a golden Syrian hamster model coinfected by SARS-CoV-2 and mouse-adapted A(H1N1)pdm09 simultaneously or sequentially. The weight loss, clinical scores, histopathological changes, viral load and titer, and serum neutralizing antibody titer were compared with hamsters challenged by either virus. Results Coinfected hamsters had more weight loss, more severe lung inflammatory damage, and tissue cytokine/chemokine expression. Lung viral load, infectious virus titers, and virus antigen expression suggested that hamsters were generally more susceptible to SARS-CoV-2 than to A(H1N1)pdm09. Sequential coinfection with A(H1N1)pdm09 one day prior to SARS-CoV-2 exposure resulted in a lower lung SARS-CoV-2 titer and viral load than with SARS-CoV-2 monoinfection, but a higher lung A(H1N1)pdm09 viral load. Coinfection also increased intestinal inflammation with more SARS-CoV-2 nucleoprotein expression in enterocytes. Simultaneous coinfection was associated with delay in resolution of lung damage, lower serum SARS-CoV-2 neutralizing antibody, and longer SARS-CoV-2 shedding in oral swabs compared to that of SARS-CoV-2 monoinfection. Conclusions Simultaneous or sequential coinfection by SARS-CoV-2 and A(H1N1)pdm09 caused more severe disease than monoinfection by either virus in hamsters. Prior A(H1N1)pdm09 infection lowered SARS-CoV-2 pulmonary viral loads but enhanced lung damage. Whole-population influenza vaccination for prevention of coinfection, and multiplex molecular diagnostics for both viruses to achieve early initiation of antiviral treatment for improvement of clinical outcome should be considered.